Building Institutions for Social Intrapreneurship - A case of practices by Business in the Community (BitC) - Umar, Zulkifli Bin (2014)
Corporate social responsibility (CSR) has received considerable renewed attention in the last few decades. With economic globalisation intensifying, there is increasing pressure for business firms to increase CSR efforts in alleviating social issues within communities that they operate. Despite the efforts by business firms with their current CSR programme initiatives, there are increasing calls for innovative solutions to alleviate the issues. To achieve this, there are institutions in the industry that lead the way in encouraging businesses to take action in response to increasing societal issues by engaging in more CSR activities.